ANALISIS KOMUNIKASI KELOMPOK DALAM MENINGKATKAN KUALITAS TEAM BIMBINGAN KERJA KETERAMPILAN KRABU DI RUTAN DEPOK KELAS 1 - Dipo Krishyudi ono; Yennie K Milono; Sabila AP Andarini (Universitas Pakuan, 2022)
This study aims to determine the group communication in improving the quality of work of Job guidance team from inmate create quality coffee they are original made, one of the important roles to keep the inmates from being aggressive and preventing behavior that causes anarchic action requires a precise communication pattern strategy approach, namely assertive communication and an activity that can get rid of negative thoughts and hone their skills. Assertive communication communicates what you think, feel, and want clearly and unequivocally to others without feeling intimidating, violating, and belittling the rights of yourself and others. The Depok Class 1 detention center has a cell block with 400 inmates out of a total of 1100 inmates who are guarded by one officer by taking turns divided into three shifts in 1 day. Inmates who are employed in detention centers or called tamping, work guidance is a form of activity to improve the abilities of inmates and help them to fill their time with positive things. The tamping in the guidance that we highlight is the specialty coffee skills section, where this coffee is one of the biggest selling commodities owned by Class 1 Depok Rutan, this is also because the tamping inmates are dedicated to making coffee with their own characteristics, namely coffee with the Krabu brand.